Social Reforms In The Period Of New Uzbekistan And The Third Renaissance (Eurasian Journal of History, Geography and Economics, 2024)
This article analyzes the processes of social reforms being implemented during the Third Renaissance of New Uzbekistan. The article examines the main changes in the areas of social protection, education, healthcare, and transparency in public administration, as well as the legal framework and practical implementation in these areas. The reforms are aimed at improving the living standards of the population and ensuring social justice